Diagnosing uncertainty, producing neonatal abstinence syndrome. (3rd January 2020) - Chandler, Amy; Whittaker, Anne; Cunningham‐Burley, Sarah; Elliott, Lawrie; Midgley, Paula; Cooper, Sarah
Abstract: The use of alcohol and other drugs during pregnancy is understood to be an important public health problem. One way in which this problem is expressed and responded to is via the identification and treatment of neonatal abstinence syndrome (NAS). In this article, we demonstrate how the processes of anticipating, identifying and responding to NAS are characterised by significant uncertainty among parents and health and social care practitioners. We draw on interviews with 16 parents who had recently had a baby at risk of NAS, and multidisciplinary focus groups with 27 health and social care professionals, held in Scotland, UK. NAS, and drug use in pregnancy, is a fraught and complex arena. Parents in the UK who use opioids risk losing custody of children, and must navigate a high degree of surveillance, governance and marginalisation. We suggest that considering NAS as a social diagnosis, further informed by Mol's political ontology of 'multiple' bodies/diseases, may help to produce clinical and social responses to uncertainty which avoid, rather than promote, further marginalisation of parents who use drugs. One such response is to develop a culture of relationship‐based care which empowers both service providers and service users to challenge existing practice and decision‐making.